Analysis of factors influencing German youth football players` club membership with a particular focus on dropout - Löbig, A.; Schlesinger, T.; Breuer, M.; Ehnold, P. (Soccer & Society, 2023)
The article explores the impact of intrapersonal, interpersonal and structural conditions as well as influences from other areas of life on youth football membership and dropout. With reference to a life course approach, football players (n = 15) from various clubs (n = 4) were interviewed using biographical mapping. Stable and unstable phases alternate in the course of a club membership. Influencing factors vary over time and mutual reinforcements can be observed. Above all, high football priority, pleasant relationships in clubs and favourable structural conditions proved to be stabilizing. In contrast, performance-related and interpersonal problems, structural deficiencies, and alternative leisure-related priorities have destabilizing effects. Four types of membership courses are identified, which are partly similar and partly differ from each other regarding relevant influencing factors. The analysis of influencing factors expands previous findings through a more process-related perspective, and therefore, provides alternative options for dealing with dropouts.